Momentum and extinction effects on self-injurious escape behavior and noncompliance. - Zarcone, J R (1994)
Previous research on applications of behavioral momentum has indicated that a high-probability (high-p) instructional sequence, in which a series of instructions for which there is a high probability of compliance is presented immediately before an instruction for which there is a low probability of compliance, is an effective method for increasing compliance. It is not clear, however, whether the procedure is effective when individuals actively attempt to escape from the instructional situation. In this study, we examined the effects of the high-p sequence, when implemented first alone and then later with an extinction component, as treatment for the self-injurious escape behavior of 2 individuals. Results showed that when the instructional sequence was implemented without extinction, rates of self-injury increased and percentage of compliance decreased. In addition, the percentage of trials occasioning escape behavior increased for both high- and low-probability instructions. When an extinction component was added to the high-p sequence, rates of self-injury and the percentage of trials containing self-injury decreased, and compliance increased. These findings suggest that extinction may be an important component of treatment when escape behavior such as self-injury accompanies noncompliance in instructional contexts and competes with compliant behavior.